2019
DOI: 10.3892/ol.2019.9896
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of OPN gene expression with proliferation and apoptosis of ovarian cancer cells and prognosis of patients

Abstract: Correlation of osteopontin (OPN) gene expression with proliferation and apoptosis of ovarian cancer cells and prognosis of patients was investigated. The expression levels of OPN in 81 pairs of ovarian cancer tissues and para-carcinoma tissues obtained via surgical resection were detected using immunohistochemistry (IHC). The correlation of OPN protein expression with clinicopathological features of patients was analyzed. All patients were followed up for 3 years. The disease-free survival (DFS) and overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Tumor apoptosis is a hallmark in the pathogenesis and treatment for human cancer patients ( 33 35 ). Li et al ( 36 ) indicated that growth arrest and apoptosis of the human hepatocellular carcinoma cell line BEL-7402 could be induced by melittin by up-regulation of Fas expression.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor apoptosis is a hallmark in the pathogenesis and treatment for human cancer patients ( 33 35 ). Li et al ( 36 ) indicated that growth arrest and apoptosis of the human hepatocellular carcinoma cell line BEL-7402 could be induced by melittin by up-regulation of Fas expression.…”
Section: Discussionmentioning
confidence: 99%
“…High plasma concentrations of SPP1 are correlated with a poor prospect for patients with head and neck cancer after radiotherapy, which can prognosticate clinically relevant hypoxia, and might determine patients who will benefit from modifying hypoxia during radiotherapy [ 8 ]. Studies have indicated that SPP1 is elevated in many malignancies, such as ovarian cancer [ 9 ], cervical cancer [ 10 ], and breast cancer [ 11 ]. And, high SPP1 expression level at the end of radiotherapy is correlated with poor survival, such as glioma [ 12 ] and non-small-cell lung cancer [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most upregulated gene in the cell adhesion pathway was SPP1, a gene that encodes for osteopontin. Osteopontin that activates interleukin 17 (IL-17) has been shown to be upregulated in ovarian cancer and important for its metastasis [ 22 ].…”
Section: Resultsmentioning
confidence: 99%